Analysis of Risk Factors for Acute Respiratory Infections in Toddlers - Fajrin Violita; Alfonsina Howay; Sherly Novita Mamoribo (Universitas Islam Negeri Alauddin Makassar, 2021)
Acute Respiratory Infection (ARI) is still one of the most common health problems caused mortality is currently high and become global concern. Diseases that attack the respiratory tract organs are caused by various factors, both internally and externally. The purpose of this study was to identify risk factors for the incidence of ARI in young children or called toodlers aged 1-5 years at the Abepura Health Center, Jayapura City. The research method used quantitative research with a cross sectional study which was carried out in January-June 2021. The research population was 937 mothers with toddlers and 90 mothers as the samples was taken by slovin formula. Data were collected through interviews using a questionnaire. Data analysis was univariate and bivariate using Chi-Square test. The results of the study found that as many as 24 toddlers (26.7%) suffered from ARI. Factors that have a significant relationship with the incidence of ARI in children under five are nutritional status of children (p-value = 0.000 < 0.05; RP = 7.16; 95% CI = (3.79 – 13.52), immunization status (p-value = 0.002 < 0.05; RP = 3.16; 95% CI = (1.69-5.89) and family smoking habits (p-value = 0.000 < 0.05; RP = 23.14; CI95% = (5 .83 – 91.82. Meanwhile, the factor of exclusive breastfeeding (p-value = 0.766 > 0.05; RP = 1.23; 95% CI = 0.60 – 2.52) was not found to be associated with the incidence of ARI. The local health center is advised to improve communication, information and education programs for mothers about the importance of maintaining nutritional status and providing complete immunizations and an approach to families to suppress smoking habits that can affect the health of toddlers.